Development of Eco-Friendly Travel Patterns based on Cultural Heritage Attractions in the City of Bandung - Dariusman Abdillah; Roby Ardiwidjaja; Marhanani Tri Astuti; Diyan Putranto (PT FORMOSA CENDEKIA GLOBAL, 2022)
Global tourism developments tend to empower the use of more environmentally friendly transportation, and tourist demand for quality tourism products is increasing. Cultural Heritage Objects are unique tourist objects, therefore, they must be managed, preserved, and utilized for the greatest prosperity of the people. The city of Bandung has a variety of fresh cultural and environmental heritage objects so that it has the potential to become an eco-friendly tourist destination. This paper aims to explain how to take advantage of cultural heritage objects as tourist attractions through the development of travel patterns using eco-friendly transportation. Data collection techniques use action research with a qualitative approach as a framework and analysis. The development of eco-friendly tourism patterns in the city of Bandung is a strategic step in the utilization of cultural heritage objects by adhering to the concept of sustainable tourism.